2020
DOI: 10.1038/s42003-020-0973-6
|View full text |Cite
|
Sign up to set email alerts
|

Cells grown in three-dimensional spheroids mirror in vivo metabolic response of epithelial cells

Abstract: Metabolism in cells adapts quickly to changes in nutrient availability and cellular differentiation status, including growth conditions in cell culture settings. The last decade saw a vast increase in three-dimensional (3D) cell culture techniques, engendering spheroids and organoids. These methods were established to improve comparability to in vivo situations, differentiation processes and growth modalities. How far spheroids mimic in vivo metabolism, however, remains enigmatic. Here, to our knowledge, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 48 publications
2
90
0
Order By: Relevance
“…Displayed data including the Gb3 profile of H1299 cells and Gb3 species of pull-down experiments were measured by targeted LC-QqQ-MS (6460, Agilent Technologies) operated in SRM/MRM mode. Chromatographic separation was achieved on a BEH C18 column (100 mm × 2.1 mm, 1.8 µm, Waters Corporation) as previously described [ 47 ]. For evaluation of the lectin preferences, cell lysates of unstimulated, LecA- and StxB-stimulated H1299 cells were split into two fractions: 10% were used to assess the Gb3 levels present in the individual sample (input).…”
Section: Methodsmentioning
confidence: 99%
“…Displayed data including the Gb3 profile of H1299 cells and Gb3 species of pull-down experiments were measured by targeted LC-QqQ-MS (6460, Agilent Technologies) operated in SRM/MRM mode. Chromatographic separation was achieved on a BEH C18 column (100 mm × 2.1 mm, 1.8 µm, Waters Corporation) as previously described [ 47 ]. For evaluation of the lectin preferences, cell lysates of unstimulated, LecA- and StxB-stimulated H1299 cells were split into two fractions: 10% were used to assess the Gb3 levels present in the individual sample (input).…”
Section: Methodsmentioning
confidence: 99%
“…First, many cell lines were established from metastatic sites and do underrepresent characteristics found in primary tumors or pancreatic intraepithelial neoplasia (PanIN) lesions [ 39 ], and second, established cell lines grow extremely fast which could easily lead to the selection of different clones and a genetic drift as reported previously [ 40 ]. Application of 3D-grown conventional cell lines can in general overcome some issues of abnormal proliferation behavior observed in 2D-cultures in comparison to in situ situations [ 41 ]. Other research systems include patient-derived xenografts (PDX).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we observed apoptotic cells mainly in the core of spheroids, with a highly proliferative outer ring. Thus, it is suggested that MCTS are more representative, also in terms of metabolism [36], compared to 2D cultured cells. This makes OS MCTS an attractive model for further pre-clinical (metabolic) drug testing.…”
Section: Conclusion and Discussionmentioning
confidence: 99%